The fate of nanomaterials - barbosa, d (2019)
Nanoscience is one of the most newsworthy research and development area in modern science andindustry. Today's manufacturing and application of nanomaterials in a wide range of areas bring specific issuesrelated to handling of waste containing nanomaterials. The outbreak that has occurred in the proliferation ofso many different engineered nanomaterials' (ENM) creates today a big issue to regulators in what concernshazard identification and environmental/ health legislation [1]. Although the majority of the scientificcommunity is yet unwilling to talk about it, is of the upmost importance to highlight problems related touncontrolled release of nanoparticles to the environment through waste disposal, and to introduce the topics ofnanowaste and toxicology of nanoparticles into the waste management. Some studies associated with usage,precautions, safety and risk perceptions related to ENM were made in some companies [2], and the resultssuggest that there is insufficient information to establish specific regulations.In order to evaluate the risks inflicted by the use of nanomaterials in commercial products, and even moreimportant, in environmental applications, is urgent to understand their mobility, bioavailability, and ecotoxicity[3]. The main concern of ENM lies in their toxicology and in the astonishing level of ENM production in theworld that leads to an increasing debate on their effects on human occupational settings and on theenvironment. As a consequence of the increasing production of NMs of all types and the potential for theirrelease in the environment, their toxicity needs to be addressed. In doing so, it is necessary first to determinethe fate and behavior of manufactured NMs in the environment. However, the mechanism of toxicity is stillunclear and biocompatibility varies depending on numerous parameters, such as nanoparticle size and shape,surface properties, applied nanoparticle concentration, type of cell and nanomaterial. The toxicity ofnanomaterials is often linked to their extremely small size; smaller particles have a greater reactive surfacearea and are more chemically reactive and produce greater numbers of reactive species, including free radicals[4]. Their high chemical reactivity and their greater capacity to penetrate biological membranes also poseserious new toxicity risks. There are now on the global market over 720 products that contain nanomaterials.Is urgent to wake-up for this new problem, that although with very small visibility (nano size), it will becomevery quickly a huge problem if we don't take the necessary attention.The present work is a review of scientific results on the fate and potential negative impact of engineerednanoparticles on the environment.